PENGARUH TUPOKSI KERJA TERHADAP SEMANGAT KERJA PEGAWAI PADA BADAN PENGELOLAAN KEUANGAN, PENDAPATAN DAN ASET DAERAH KOTA SIBOLGA - Amaludin Sikumbang (Universitas Pahlawan Tuanku Tambusai, 2022)
In general, the purpose of this study was to determine the effect of the main tasks and functions on employee morale at the Financial Management Agency, Regional Revenue and Assets of Sibolga City. The method used is descriptive correlational method. The description method is an explanation or explanation of research results obtained through questionnaires distributed to respondents. The results of the study include gender, education level, age and the average interpretation of respondents' answers for each item. While correlational to find out how much influence the independent variables have on the variables used by the simple linear regression analysis method and the calculation of the coefficient of determination, to test the ability of independent variations to explain the variation of variables in the model. The author uses 55 respondents as a sample taken from all employees. The results of the determination coefficient research show that the job duties of employees are 60% of the morale of employees at the Regional Finance, Revenue and Assets Agency of Sibolga City and the remaining 40% is determined by other variables. The results showed that there was a significant relationship between the main duties of the employee and the morale of the employees at the Regional Finance, Revenue and Assets Agency of Sibolga City of 0.755, so that if interpreted on a scale it could be categorized as high correlation. The regression equation obtained is Y= 24,566 + 0.485X. The t test shows that t count is greater than t table or (8.942 > 2.00575). Because the t-count value is greater than the t-table value, the significant relationship and the hypothesis proposed in Chapter - I can be accepted. Keywords: Job Duties and Morale